A randomized phase II study of S-1 versus capecitabine as first-line chemotherapy in elderly metastatic gastric cancer patients with or without poor performance status: clinical and pharmacogenetic results. Issue 1 (January 2018) - Kim, Mi-Jung; Kong, Sun-Young; Nam, Byung-Ho; Kim, Sohee; Park, Young-Iee; Park, Sook Ryun
Abstract : Objective: This study investigated the efficacy and safety of S-1 versus capecitabine in elderly patients with metastatic gastric cancer (MGC), and examined the association between cytochrome P450 2A6 ( CYP2A6 ) polymorphisms and treatment outcomes. Materials and methods: MGC patients 70–85 years old with Eastern Cooperative Oncology Group (ECOG) performance status 0–2 or 65–70 years old with ECOG PS 2 were randomized to receive S-1 40 mg/m 2, twice daily, or capecitabine 1250 mg/m 2, twice daily, on days 1–14 every 3 weeks. Results: From May 2007 up to July 2010, 107 patients were enrolled. G3/4 neutropenia developed in 3.8% of each arm, and the most common G3/4 nonhematological toxicities were anorexia and fatigue. Vomiting and tearing were more frequent with S-1 and hand–foot syndrome with capecitabine. The primary endpoint, the overall response rate, was 26.4% (14/53, 95% confidence interval: 14.5–38.3%) in S-1 and 24.1% (13/54, 95% confidence interval: 12.7–35.5%) in capecitabine, both of which exceeded the null hypothesis response rate of 10%. The median time to progression (TTP; 3.2 vs. 3.4 months, P =0.813) and overall survival (OS; 8.5 vs. 10.3 months, P =0.691) were similar in both arms. CYP2A6 polymorphisms were associated with S-1 efficacy. In the S-1 arm only, patients with CYP2A6 variant/variant alleles had worse TTP and OS than those with wild/wild or wild/variant alleles, and in multivariate analysis, the CYP2A6 genotype was predictive for TTP and OS. Conclusion: Both S-1 and capecitabine were active and tolerable for elderly MGC patients. The CYP2A6 genotyping might guide treatment selection. Abstract : Supplemental Digital Content is available in the text.